Role of Integrin αvβ3 in Doxycycline-Induced Anti-Proliferation in Breast Cancer Cells - Chen, Yi-Fong; Yang, Yung-Ning; Chu, Hung-Ru; Huang, Tung-Yung; Wang, Shwu-Huey; Chen, Han-Yu; Li, Zi-Lin; Yang, Yu-Chen S. H.; Lin, Hung-Yun; Hercbergs, Aleck; Whang-Peng, Jacqueline; Wang, Kuan; et al. (Frontiers in Cell and Developmental Biology, 2022)
Doxycycline, an antibiotic, displays the inhibition of different signal transduction pathways, such as anti-inflammation and anti-proliferation, in different types of cancers. However, the anti-cancer mechanisms of doxycycline via integrin αvβ3 are incompletely understood. Integrin αvβ3 is a cell-surface anchor protein. It is the target for estrogen, androgen, and thyroid hormone and plays a pivotal role in the proliferation, migration, and angiogenic process in cancer cells. In our previous study, thyroxine hormones can interact with integrin αvβ3 to activate the extracellular signal-regulated kinase 1/2 (ERK1/2), and upregulate programmed death-ligand 1 (PD-L1) expression. In the current study, we investigated the inhibitory effects of doxycycline on proliferation in two breast cancer cell lines, MCF-7 and MDA-MB-231 cells. Doxycycline induces concentration-dependent anti-proliferation in both breast cancer cell lines. It regulates gene expressions involved in proliferation, pro-apoptosis, and angiogenesis. Doxycycline suppresses cell cyclin D1 (CCND1) and c-Myc which play crucial roles in proliferation. It also inhibits PD-L1 gene expression. Our findings show that modulation on integrin αvβ3 binding activities changed both thyroxine- and doxycycline-induced signal transductions by an integrin αvβ3 inhibitor (HSDVHK-NH2). Doxycycline activates phosphorylation of focal adhesion kinase (FAK), a downstream of integrin, but inhibits the ERK1/2 phosphorylation. Regardless, doxycycline-induced FAK phosphorylation is blocked by HSDVHK-NH2. In addition, the specific mechanism of action associated with pERK1/2 inhibition via integrin αvβ3 is unknown for doxycycline treatment. On the other hand, our findings indicated that inhibiting ERK1/2 activation leads to suppression of PD-L1 expression by doxycycline treatment. Furthermore, doxycycline-induced gene expressions are disturbed by a specific integrin αvβ3 inhibitor (HSDVHK-NH2) or a mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinases (ERK) kinase (MAPK/ERK, MEK) inhibitor (PD98059). The results imply that doxycycline may interact with integrin αvβ3 and inhibits ERK1/2 activation, thereby regulating cell proliferation and downregulating PD-L1 gene expression in estrogen receptor (ER)-negative breast cancer MDA-MB-231 cells.